Endoscopic Study of the Oral and Pharyngeal Cavities in the Common Dolphin, Striped Dolphin, Risso’s Dolphin, Harbour Porpoise and Pilot Whale: Reinforced with Other Diagnostic and Anatomic Techniques - Álvaro García de los Ríos y Loshuertos; Marta Soler Laguía; Alberto Arencibia Espinosa; Francisco Martínez Gomariz; Cayetano Sánchez Collado; Alfredo López Fernández; Francisco Gil Cano; Juan Seva Alcaraz; Gregorio Ramírez Zarzosa (Animals, 2021)
In this work, the fetal and newborn anatomical structures of the dolphin oropharyngeal cavities were studied. The main technique used was endoscopy, as these cavities are narrow tubular spaces and the oral cavity is difficult to photograph without moving the specimen. The endoscope was used to study the mucosal features of the oral and pharyngeal cavities. Two pharyngeal diverticula of the auditory tubes were discovered on either side of the choanae and larynx. These spaces begin close to the musculotubaric channel of the middle ear, are linked to the pterygopalatine recesses (pterygoid sinus) and they extend to the maxillopalatine fossa. Magnetic Resonance Imaging (MRI), osteological analysis, sectional anatomy, dissections, and histology were also used to better understand the function of the pharyngeal diverticula of the auditory tubes. These data were then compared with the horse’s pharyngeal diverticula of the auditory tubes. The histology revealed that a vascular plexus inside these diverticula could help to expel the air from this space to the nasopharynx. In the oral cavity, teeth remain inside the alveolus and covered by gums. The marginal papillae of the tongue differ in extension depending on the fetal specimen studied. The histology reveals that the incisive papilla is vestigial and contain abundant innervation. No ducts were observed inside lateral sublingual folds in the oral cavity proper and caruncles were not seen in the prefrenular space.